Determination of the Location of Fishing Boat Moorings in Palu Bay After The 2018 Tsunami in Terms of Technical and Socio-Economic Aspects. Issue 1 (1st November 2022) - Amar,; Rusdin, A; Setiyawan,; Arifin, S; Saleh, M; Sri, N A
Abstract: The natural disaster that occurred in Palu City, Donggala and Sigi Regencies on September 28, 2018 in the form of an earthquake accompanied by a tsunami and liquefaction was one of the phenomena that was considered quite interesting because it had never happened in any area in Indonesia. The existence of three types of natural disasters that occur at the same time has an impact on people's lives and is interesting to study so that anticipation and solutions can be considered in the future. This condition will certainly have a direct impact on the mooring of fishing boats in Palu Bay. Thus, a location determination is needed and a review of technical, social and economic aspects is needed. So we need an effort to involve academics in recording and providing solutions to increase marine products after the earthquake. The purpose of this service is to plan fishing boat moorings after the earthquake and liquefaction which aims to find out the right position so that it can be utilized by fishermen, provide knowledge to fishermen that the use of existing boat moorings must be done to improve their economy and make boat moorings more efficient. provide education about fisherman productivity. The specific target to be achieved is to determine the location of fishing boat moorings after the earthquake, to be able to contribute to the Palu City Government, especially the River Region III Center so that they can design boat moorings on each coast, through the Palu City Government master plan to provide a post-earthquake response stimulus to helping fishing communities to rise and is expected to increase the productivity of fishermen.